Understanding intention to quit amongst artisans and engineers: The facilitating role of commitment - Samuel Siwela; Francois van der Bank (SA Journal of Human Resource Management, 2021)
Orientation: Given the critical shortage of skilled artisans and engineers in the job market, retention of this key talent is of paramount importance.